Value-Based CEO Equity Grants - Xu, Jin; Ye, Pengfei; Zhang, Cheng (Journal of Financial and Quantitative Analysis, 2025)
Abstract We document firms often determine CEO equity grants based on a predetermined dollar value (value-based equity grant) instead of on the number of shares (share-based grant). Value-based equity grants weaken the relationship between stock performance and CEO equity pay, lower CEO portfolio delta, and slow firms’ investment in R&D. We find that retention pressure is a key reason for the use of value-based equity pay, while governance could also matter. Overall, this paper alerts boards to the unintended consequences of pursuing a target pay level or pay structure because such practices can lead to value-based equity grants in CEO compensation.